In Vitro Anti-Vibrio Activity of Miana Leaves (Coleus scutellarioides (L) Benth) - Basir, Buana; Alim Isnansetyo; Indah Istiqomah (JFMR (Journal of Fisheries and Marine Research), 2024)
The aim of this research is to determine the bioactive compounds of miana leaves of Coleus scutellarioides (L) Benth against Vibrio spp.. This research was carried out from April to August 2018 at the Fish Pests and Diseases Laboratory, Department of Fisheries, Gadjah Mada University. Miana leaf samples were dried at room temperature, macerated with ethanol solvent and tested for antibacterial activity. Separation of bioactive compounds was carried out using liquid partition and silica gel using the column chromatography method. MIC (minimum inhibitory concentration) is applied to evaluate antibacterial activity. The results showed that the highest antibacterial activity was found in the chloroform fraction with inhibitory zone diameters for V. parahaemolitycus, V. alginolitycus, and V. harveyii of 25 mm, 26 mm, and 20 mm at a dose of 20 µg/disk. These findings indicate that the antibacterial activity of miana leaf crude extract is comparable to oxytetracycline with inhibition zones of 25 mm, 31 mm and 20 mm respectively against similar bacterial strains at 20 µg/disk. Therefore, miana leaves are a prospective natural source of anti-vibrio compounds.